PENGARUH MEDIA PERMAINAN ULAR TANGGA TERHADAP KEMAMPUAN MEMBACA PADA ANAK KELOMPOK B DI TK FATIMA GELURAN - Surya Devi Setianingsih; Isabella Hasiana; Aulia Insani (Program Studi PG-PAUD Universitas PGRI Adi Buana Surabaya, 2022)
This research was motivate by the lack of reading abilitys in group B children in TK Fatima Geluran. The low reading ability of children as a result of the learning method used by the teacher does not provide maximum results. The use of snake and lader game media researchers chose as one of the solutions, because snake and ladder game media has a positive impact on increasing children's reading skills. The formula of the problems in this study, is there any influences of snake and ladder game media on reading ability in group B children in Fatima Geluran. The purposes of this research is to finds out whethers theres is an effect of snake and ladder games media on reading ability in group B children in Fatima Geluran. The types of research that the author used is quantitatives with the types of one groups pretest-posttest design. The data collections technique used is observations and processed by Pair Sample T Test. The result show that there was a significant increased in the snake and ladder game media on children's reading ability, with df or db 11, if we look at the t-value table with a significant level of 5%, the